The Margins of Labor Cost Adjustment : Survey Evidence from European Firms - Babecky, Jan; Du Caju, Philip; Kosma, Theodora; Lawless, Martina; Messina, Julian; Room, Tairi (World Bank, Washington, DC, 2014)
Firms have multiple options at the time of adjusting their wage bills. However, previous literature has mainly focused on base wages. This paper broadens the analysis beyond downward rigidity in base wages by investigating the use of other margins of labor cost adjustment at the firm level. Using data from a unique survey, the authors find that firms make frequent use of other, more flexible, components of compensation to adjust the cost of labor. Changes in bonuses and non-pay benefits are some of the potential margins firms use to reduce costs. The paper also shows how the margins of adjustment chosen are affected by firm and worker characteristics.